Paddling the Salish Sea : 80 trips in Puget Sound, the San Juan Islands, Olympic Peninsula & southern British Columbia - Casey, Rob (Mountaineers Books, 2024)
"Professional kayaker and paddling coach Rob Casey guides paddlers to the most rewarding destinations across the region. Paddles range from protected lakes and short routes for beginners to more exposed, longer saltwater trips for advanced paddlers. Includes detailed information on paddle duration, difficulty, and planning considerations plus paddling safety, gear, trip planning, and more. For sea or flatwater kayakers, canoeists, rowers, or stand-up paddle boarders"--